DEPENDENCE OF THE STUDENTS 'MENTAL PERFORMANCE ON THE LEVEL OF THEIR PHYSICAL PREPAREDNESS - Koroev, A.G; Bazrova, L.R (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
Physical culture and sports in high school, as one of the main means of educating students of a valuable attitude to a healthy lifestyle, improving the coordination of their movements, developing the necessary motor skills and skills, is aimed at developing the vital personality qualities necessary for successful adaptation as changes in educational process, and to all changes in educational and professional activities. Properly organized exercise exercises strengthen the physiological, mental and somatic health of a person, increase his mental and physical activity. The influence of exercise on the formation of personality is a factor of social importance. In this regard, classes in physical culture and sport are a certain form of educational activity, which contains elements of a direct impact on the development of the personality of the student - the future competence specialist. A specific feature of physical culture classes is that they stimulate the processes of self-knowledge and self-improvement of students. Students learn to manage their mood, cope with excessive anxiety, master the ability of self-management, self-regulation of emotions. The possibility of using physical culture tools for students' self-improvement, preparing them for present and future educational and professional activities lies in the very specifics of physical exercise as an activity. The development of students mental, physical and motor skills, the improvement of mental processes, ranging from relatively simple, at the level of psychomotor, and ending with the most complex, intellectual, at the level of thinking and imagination. Regular physical activity creates an opportunity for the development and improvement of students' will.